From Controversy to Credibility: The Crucial Role of Spokespersons in the Digital Age - Butarbutar, Benny Siga (Ikatan Sarjana Komunikasi Indonesia, 2025)
One of the main challenges facing spokespersons in the digital era is the intensity of media and public spotlight and scrutiny in which any statement will be analyzed and criticized openly. The other equally important challenges are keeping message consistency in various digital platforms and ensuring harmony with the core values of the organization. Answering journalists is nothing more than a technical affair but requires tranquility, a holistic mind, and deep knowledge about the context of the surrounding situation. In transparency pressure, spokespersons are not easy because they must be able to keep a balance between information transparency and policy in maintaining the integrity of sensitive data. Digital platform transformation has decentralized information flow, strengthened public skepticism, and increased the risk of social conflict as a result of controversial speech or video. Additionally, it has brought about a serious implication on speech etiquette. In this context, the application of strategic communication becomes a crucial strategy in the digital age, requiring approaches that are not merely reactive but also systematically designed, adaptive to the emerging dynamics, measurable to achieve it, and constantly based on strong communication ethics. Moreover, strategic communication plays a significant role in strengthening institutional legitimacy and building enduring public trust in the long run. These research findings underscore the need to develop a collaborative, cross-functional, and cross-sectoral strategic communication ecosystem in order to improve the effectiveness of message delivery and the credibility of the institution in responding to communication challenges that demand speed, real-time, transparency, and social sensitivity.